Alfredo Breceda: protagonist and witness of Mexican revolution war (Tzintzun, Revista de Estudios Históricos, 2016)
The historical work of Alfredo Breceda remains unrecognized. The yore and con-temporary Mexican revolution historiography has not taken him and many othersinto account. Altogether men, women and children who witnessed the Mexicanrevolution war remain unknown. Mexico revolucionario, his masterpiece, it is anattempt to show an objective and well presented political history of the early yearsof the Mexican revolution as well as the beginnings of the first constitutionaliststage. Despite he was Venustiano Carranza follower, he attempted to avoid andovercome the influences that made him to be less objective and un:torical testimony. The first volume was published in 1920, and the second one in1941, that’s why his books clearly shows a tour of the main military, diplomaticand gubernatorial events of the revolutionary leaders.
Keywords: Breceda; historiographie; Révolution mexicaine